Dibutyryl‐cAMP and roscovitine differently affect premature meiotic resumption and embryo development of vitrified immature porcine oocytes. (23rd December 2022) - Nguyen, Hiep Thi; Somfai, Tamás; Hirao, Yuji; Dang‐Nguyen, Thanh Quang; Linh, Nguyen Viet; Nguyen, Bui Xuan; Nguyen, Nhung Thi; Nguyen, Hong Thi; Nguyen, Van Hanh; Kaneko, Hiroyuki; Takagi, Mitsuhiro; Kikuchi, Kazuhiro
Abstract: Vitrification and warming can trigger premature meiosis in immature porcine oocytes. Our aim was to compare the efficacies of two meiotic inhibitors, dibutyryl‐cAMP and roscovitine for the meiosis synchronization during in vitro maturation (IVM) of porcine oocytes vitrified at the germinal vesicle (GV) stage. We first compared the efficacy of 1 mM dibutyryl‐cAMP and 25 μM roscovitine on meiotic arrest during the first 22 h of IVM. Dibutyryl‐cAMP could maintain the GV stage in 83.5% of oocytes; however, roscovitine was even more effective (96.6%), whereas only 17.4% of the oocytes remained at the GV stage without these additives. Temporal meiotic arrest for 22 h by roscovitine did not reduce the percentage of oocytes reaching the Metaphase II stage during subsequent IVM. However, after parthenogenetic stimulation or in vitro fertilization, subsequent embryo development to the blastocyst stage was compromised after roscovitine treatment, whereas dibutyryl‐cAMP improved the percentage of blastocyst development. In conclusion, dibutyryl‐cAMP could derogate but not completely prevent premature meiosis in vitrified oocytes, whereas roscovitine could more efficiently prevent it. However, for embryo production, the use of roscovitine was disadvantageous, whereas the use of dibutyryl‐cAMP was beneficial.